Fostering Social Justice through Service-Learning in Early Childhood teacher education - Christian Winterbottom; Vickie E. Lake; Elizabeth A. Ethridge; Loreen Kelly; Jessica L. Stubblefield (Universidad Autónoma de Madrid, 2015)
As early childhood teacher education programs have begun to place greater emphasis on standards and accountability, there has been less focus on working with the community, and especially working on important social justice issues (Kroll, 2013). In this paper we argue that integrating service-learning and teacher education is a strategy for increasing awareness of social justice issues for young children, age three to grade three. Through the use of questionnaires and interviews to collect our data, we found that implementing a cascading service-learning model in teacher education programs has a positive transformative effect on Pre-Service Teachers. Additionally, we examined the effects of social justice service-learning projects on young children. The results from the data indicated that implementing a social justice service-learning project with these participants had a great impact or transformation on them.